Website-Based Teaching Material Development to Improve Student Mathematics Learning Outcomes - Muhammad Azhar Mushoffa; Hendri Raharjo; Alif Ringga Persada (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
The very rapid development of science and technology offers us various conveniences. Teaching materials that are made are the website at the web address belajarmatematics.id. The objectives of this study are: 1) To determine the effectiveness of website-based teaching materials. 2) determine student responses to website-based teaching materials applied in schools. 3) determine the increase in student mathematics learning outcomes using website-based teaching materials. The research method used in this study is RnD (Research and Development) with the ADDIE model with data collection techniques using questionnaires and tests. The sample used was class VII F SMP Negeri 1 Krangkeng, Indramayu Regency. Based on the results of the independent sample t test (two tailed), it can be seen that the value of tcount> ttable, is 6.331> 2,000. Because tcount> ttable, it means that there is a difference in students' mathematics learning outcomes between using website-based teaching materials and without web-based teaching materials. Student responses to the application of website-based mathematics teaching materials show strong criteria with an average of 85.08%. The average gain score of students using website-based teaching materials is 0.67 or 67%.